Specificity of Genetic Biomarker Studies in Cancer Research: A Systematic Review. - Garrett Green; Ruben Carmona; Kaveh Zakeri; Chih-Han Lee; Saif Borgan; Zaid Marhoon; Andrew Sharabi; Loren K Mell (PLoS ONE, 2016)
As genetic information becomes more readily available, there is increasing demand from both patients and providers to develop personalized approaches to cancer care. Investigators are increasingly reporting numbers of studies correlating genomic signatures and other biomarkers to survival endpoints. The extent to which cancer-specific and non-specific effects are reported in contemporary studies is unknown. In this review of 85 high-impact studies associating genetic biomarkers with cancer outcomes, 95% reported significant associations with event-free survival outcomes, yet less than half reported effects on a cancer-specific endpoint. This methodology leaves open the possibility that observed associations are unrelated to cancer.